2019
DOI: 10.1155/2019/2915684
|View full text |Cite|
|
Sign up to set email alerts
|

Durability of GFRC Modified by Calcium Sulfoaluminate Cement under Elevated Curing Temperatures

Abstract: CSA/GFRC is an advanced composite material possessed with great ductility and durability. However, its bending performance and fibre condition, as well as intrinsic microstructural changes, under elevated temperature have not been understood so far. XRD was applied in this study to investigate the hydration mechanism of CSA cement under 50°C, 70°C, and 80°C. Bending performance was carried out to test the toughness of CSA/GFRC. SEM was applied to observe the underlying microstructural changes of CSA/GFRC under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 22 publications
3
4
0
Order By: Relevance
“…It can be found out that low-temperature environments have very little effect on the type of hydration products of CSA modified cement. Crystalline CH is still absent, and large amounts of ettringite can be traced in all the specimens of CSA modified cement under low-curing temperatures, which is in agreement with the previous research [14,16]. e sharp peak of ettringite in the CSA paste cured at −5 °C suggests that hydration of CSA cement still continues at lower temperature, which is beneficial for the development of both strength and densified microstructure.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…It can be found out that low-temperature environments have very little effect on the type of hydration products of CSA modified cement. Crystalline CH is still absent, and large amounts of ettringite can be traced in all the specimens of CSA modified cement under low-curing temperatures, which is in agreement with the previous research [14,16]. e sharp peak of ettringite in the CSA paste cured at −5 °C suggests that hydration of CSA cement still continues at lower temperature, which is beneficial for the development of both strength and densified microstructure.…”
Section: Resultssupporting
confidence: 91%
“…is degradation process is similar to the previous results on CSA/GFRC [5,16], in which CSA/GFRC indicates gradual and medium reduction on both strength and ductility under accelerated ageing.…”
Section: Stress-strain Performancesupporting
confidence: 89%
See 2 more Smart Citations
“…Hydrated cement paste is a brittle material with low tensile strength and inferior resistance to crack propagation. Previous studies showed that its toughness would be improved by the addition of fiber reinforcements (Brandt, 2008;Song et al, 2019). Fibres can not only limit the crack expansion but can also withstand the external loads mutually with cement.…”
Section: Introductionmentioning
confidence: 99%